(untitled) - Joyce, J. D. (Hoboken, N.J., 2012)
An investing story that provides insights into dealing with your money and finding financial securityMaking the right investment decisions and executing an effective financial plan can be difficult, especially in today's markets. But with the right guidance you can achieve this goal. Now, in Financial Crossings, leading wealth manager John "J.D." Joyce shows you how. Based on his real-world experiences with investors throughout his successful career, this book offers meaningful advice about financial planning and investing.Designed for those with significant assets who are nearing or recently retired, as well as individuals who have recently come into new money through business or inheritance, Financial Crossings skillfully explains financial planning and investing through a fable of a man who sells a business he's worked so hard to build, and now finds himself with more money then he's ever had to deal with. Along the way, this book teaches you about important investment concepts and presents you with tools to consider your options and choose an appropriate investment strategy. Chronicles the fictional story of a recently retired businessman who is worried about making the most of his money now that he's no longer generating regular income Presents lessons about investing, sometimes through comparisons to topics like marathon running or wine making, in the quest to make sense of fundamental investment concepts Author John "J.D." Joyce has been named a Top Financial Advisor by Barron's for three years running Engaging and informative, Financial Crossings is the perfect guide for those concerned about protecting their hard-earned money and investing it wisely
Keywords: Investments,Đầu tư